2015
DOI: 10.1016/j.neuropharm.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1-mediated ATP release from area CA3 drives mGlu5-dependent neuronal oscillations

Abstract: The activation of Group I metabotropic glutamate receptors (GI mGluRs) in the hippocampus results in the appearance of persistent bursts of synchronised neuronal activity. Such activity is known to cause the release of the purines ATP and its neuroactive metabolite, adenosine.We have investigated the role of the purines in GI mGluR-induced oscillations in hippocampal areas CA3 and CA1 using pharmacological techniques and microelectrode biosensors for ATP and adenosine. The GI mGluR agonist DHPG induced both pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…This work has been conducted in wild-type and genetically-modified rodent parasagittal hippocampal and neocortical slices. A thickness of 600 µm is required for hippocampal slices, as opposed to the standard 300 -400 µm, as we find thinner rat slices do not support electrically-evoked seizure activity (Etherington and Frenguelli, 2004) or that induced by the GI mGluR agonist DHPG (Lopatar et al, 2015). We avoid hypoxia in the core of the slice by suspending the slice upon a mesh in the recording chamber and perfusing the submerged tissue on both sides, using gas-impermeable tubing and perfusing aCSF at ~6 ml/min (Etherington and Frenguelli, 2004;Wall and Richardson, 2015).…”
Section: The Application Of Biosensors To Study Seizuresmentioning
confidence: 71%
See 3 more Smart Citations
“…This work has been conducted in wild-type and genetically-modified rodent parasagittal hippocampal and neocortical slices. A thickness of 600 µm is required for hippocampal slices, as opposed to the standard 300 -400 µm, as we find thinner rat slices do not support electrically-evoked seizure activity (Etherington and Frenguelli, 2004) or that induced by the GI mGluR agonist DHPG (Lopatar et al, 2015). We avoid hypoxia in the core of the slice by suspending the slice upon a mesh in the recording chamber and perfusing the submerged tissue on both sides, using gas-impermeable tubing and perfusing aCSF at ~6 ml/min (Etherington and Frenguelli, 2004;Wall and Richardson, 2015).…”
Section: The Application Of Biosensors To Study Seizuresmentioning
confidence: 71%
“…Indeed, in a more recent study, we have observed that the application of the GI mGluR agonist DHPG elicits burst firing in area CA1, which is associated with adenosine release from areas CA1 and CA3, but ATP release from only area CA3 (Figure 7) (Lopatar et al, 2015). Importantly, ATP release, but not the release of adenosine, was greatly suppressed by either probenecid or a low concentration of carbenoxolone, suggesting both a spatial and mechanistic dissociation between ATP and adenosine release, and the release of ATP via pannexin-1 hemichannels.…”
Section: Insight Into the Regulation Of Basal And Seizure-induced Purmentioning
confidence: 84%
See 2 more Smart Citations
“…Biosensors have been used to measure neurotransmitters and neuromodulators including glutamate (Hu et al 1994; Oldenziel et al 2006; Tian et al 2009), acetylcholine (Bruno et al 2006; Zhang et al 2010), adenosine triphosphate (Llaudet et al 2005; Frenguelli et al 2007; Gourine et al 2008; Lalo et al 2014; Lopatář et al 2015; Wells et al 2015), glucose (Lowry et al 1998; Dash et al 2013), adenosine, inosine, and hypoxanthine (Llaudet et al 2003; Klyuch et al 2012; Dale 2013; Van Gompel et al 2014; Wall and Richardson 2015; Frenguelli and Wall 2016). Many microelectrode biosensors developed for brain tissue use oxidative enzymes followed by detection via fixed-potential amperometry.…”
mentioning
confidence: 99%